Exploring memorable tourism experiences and revisit intentions of Langkawi Island: a conceptual model development / Nurzehan Abu Bakar, Hassnah Wee and Mohd Hafiz Mohd Hanafiah - Abu Bakar, Nurzehan; Wee, Hassnah; Mohd Hanafiah, Mohd Hafiz (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
For many years, Langkawi Island has been known as a tourist paradise because of its sun, sand, and sea (3s) attractions. Making it the best destination for tourists who want to immerse themselves in island life and have unique, memorable experiences. Despite its beautiful setting, many tourists thought Langkawi was dull and uninteresting because there aren't many experiences offered on the island. Furthermore, little study has been conducted to determine travellers' intention to revisit an island in the future based on a Memorable Tourism Experience (MTE) model. Hence, a conceptual framework to investigate MTEs and revisit intention is proposed. The findings of this study are significant in assisting tourism stakeholders in strategising tourism experience marketing and contributing to the tourism literature.